192 Does socioeconomic status impact on the prescription of disease-modifying treatments in people with multiple sclerosis?. Issue 12 (14th November 2019) - Reyes, Saúl; Allen-Philbey, Kimberley; Suarez, Sebastian; Yildiz, Özlem; Turner, Ben; Gnanapavan, Sharmilee; Schmierer, Klaus; Marta, Monica; Mathews, Joela; Giovannoni, Gavin
Abstract : Objective: To examine the association between socioeconomic status (SES) and prescription of disease-modifying treatments (DMTs) in people with multiple sclerosis (pwMS). Methods: A cross-sectional study was conducted among 734 pwMS aged ≥18 years attending the neuroinflammation service at The Royal London Hospital (Barts Health NHS Trust) between 1997 and 2017. SES was determined by patient income and education extracted from the English Index of Multiple Deprivation. Multinomial logistic regression was performed to assess differences between SES and prescription of DMTs. Results: DMTs were categorized as follows: moderate efficacy therapies included Glatiramer Acetate and Beta-Interferons (n=81, 11.04%), high efficacy therapies included Cladribine, Fingolimod and Dimethyl Fumarate (n=409, 55.72%), and very-high efficacy therapies included Natalizumab and Alemtuzumab (n=244, 33.24%). Medians for income and education deciles were 4 (IQR 3–7) and 6 (IQR 4–8), respectively. Patient income was not associated with increased odds of being prescribed high efficacy (OR, 1.02; 95% CI, 0.91–1.14; p=0.814) or very-high efficacy DMTs (OR, 1.01; 95% CI, 0.90–1.14; p=0.732). Similarly, patient education was not associated with the prescription of high efficacy (OR, 0.96; 95% CI, 0.84–1.10; p=0.585) or very-high efficacy DMTs (OR, 0.96; 95% CI, 0.84–1.10; p=0.538). Conclusions: SES was not predictive of prescription of DMTs in this single-centre study. It would be of interest to compare our data with other MS services, and to map these results onto the inequity in access to DMTs across the UK.